2016
DOI: 10.1186/s12995-016-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Health status of male steel workers at an electric arc furnace (EAF) in Trentino, Italy

Abstract: BackgroundThe aim of this retrospective cohort study was to determine if the workers of an Electric Arc Furnace (EAF), which recycles scrap, had higher mortality and morbidity due to possible exposure to pollutants at work. EAFs do not run on coke ovens. In EAFs 40 % of the particulate matter (PM) is made up of PM 2.5. The foundry dust contained iron, aluminum, zinc, manganese, lead, chromium, nickel, cadmium, mercury, arsenic, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls and dioxins.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Clear associations between chronic disease and occupations with cadmium inhalation as described by Cappelletti et al [ 1 ] and others [ 3 5 ] have been demonstrated. Further epidemiological work related to occupational cadmium exposure and disease development, particularly with regard to RA, is required to modify behaviour influencing development of future chronic disease.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Clear associations between chronic disease and occupations with cadmium inhalation as described by Cappelletti et al [ 1 ] and others [ 3 5 ] have been demonstrated. Further epidemiological work related to occupational cadmium exposure and disease development, particularly with regard to RA, is required to modify behaviour influencing development of future chronic disease.…”
Section: Discussionmentioning
confidence: 86%
“…We read with interest by Cappelletti et al “Health status of male steel workers at an electric arc furnace in Trentino, Italy [ 1 ]”. The authors demonstrated significantly increased disease risk; specifically, rheumatoid arthritis (RA), hypertension and cardiovascular diseases in exposed workers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] suggest an OR of 2.6 (OR 1.0-7.4) for ACPA+ RA in smelters and metal foundry workers. A retrospective cohort study of workers recycling scrap metals at an electrical arc furnace in Italy noted 3/331 incident cases of RA over a 20 year follow up period, a dramatically increased RR of 6.18 (95%CI 2.00-19.02), when compared to 420/20332 incident RA cases in the same town over the same period [ 33 ]. Despite the relatively small sample size and lack of directly comparable working group, this cohort demonstrated an appreciably elevated RA risk, thought due to foundry dust exposure containing a range of potential toxins including heavy metals [ 34 ].…”
Section: Inhalational Workplace Exposuresmentioning
confidence: 99%
“…Heavy metals: Numerous studies indicated an association between heavy metals and insulin resistance (cardio-vascular diseases and diabetes) [122][123][124][125][126][127] explained by their direct effects on ROS production and inflammatory mediated cellular and systemic damage, decreased mitochondrial function with reduction of the capacity for fatty acid oxidation, inhibition of lipoprotein lipase in adipocytes and β-cells destruction [128]. Maternal gestational diabetes is also increased by heavy metal exposure [129].…”
Section: Chemical Hazards and Air Pollutionmentioning
confidence: 99%